The Examining The Clinical Nutrition Internship Effectiveness from Interns' Perceptions - Afrah Alhur; Anas Alhur; Dalal Nabit Alanazi‎ (International Journal of Education, Teaching, and Social Sciences, 2022)
Through internship programs, students can acquire practical experience while learning from experts. Students can gain hands-on experience while combining theory and practice. This study examines the clinical nutrition internship program at the University of Hail in Saudi Arabia. Another objective of this study is to examine how interns perceive the internship program. Clinical nutrition students were surveyed online using social media platforms and specialized groups. This study involved 40 clinical nutrition interns in 2022/3/7. All of the interns were from the University of Hail. In this study, interns indicated that the internship positively impacted their learning, interpersonal, and personal skills and their employment prospects. For instance, 50% reported the availability of site supervisors when needed. Furthermore, 90% of the respondents indicated having the ability to persevere in complex tasks. Moreover, 90% illustrated that they acquired knowledge from the job duties. Further research is required to identify the barriers associated with this issue. According to the researchers, clinical nutrition, and other departments in the college of applied medical sciences curriculum should integrate soft skills. The supervisor should have a thorough understanding of the health informatics field and the intern's responsibilities. This will enable them to help the intern put what they learned in class into practice. The findings of this study can be used to study health informatics internships in greater depth. We strongly recommend conducting a comparative study with more participants from diverse institutions.